Mediebrud mellem organisationer og netværk [Media disruptions between organisations and networks] - Clausen, Lars (MedieKultur: Journal of media and communication research, 2010)
The present article examines the elites’ dependence on diffusion media and communication media within the Luhmannian system theory. Through the use of a media concept from medium-theory and concepts from research on elites, three levels of dependency emerge: the diffusion media, the media of the system and leadership as the specific communication medium of elites, which is dependent on the state of the three media. The hypothesis is that the specific form of elites has specific, epochal media dependencies, and this becomes evident in the present in social scientific research.